A Systematic Review for The Development of Sustainable Tourism Destinations Based on Sports Tourism - Eko Sudarmanto; Bambang Budi Raharjo; Agus Kristiyanto; Sulaiman Sulaiman; Heny Setyawati; Bambang Priyono; Gatot Jariono (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The study purpose: The project's goal is to develop sustainable tourism destinations in Kemuning Village by reviewing the literature on sports tourism Materials and methods: An extensive literature review was carried out. Articles from 2015 to 2024 covered ways to enhance sustainable tourism by fostering the growth of sports tourism. For electronic searches, Google Scholar, PubMed, Web of Science, and Scopus are used. All the articles that discuss how to improve sports tourism-based tourist attractions are included here. Results: According to the integrated theory of tourism, sports have a role in (1) tourism management strategies, which include methods, facilities, tourist attractions, SOPs, infrastructure, additions and maintenance of facilities, sustainable management of natural resources, and visitor security and safety; (2) the role of stakeholders, which includes the government as a regulator and related institutions; and (3) the role of the authorities, which includes government agencies and institutions related to Sports tourism will increase visits to Central Java and improve the economy. Sports activities in tourist destinations can benefit local governments, enhance community welfare, and create more job opportunities if they are appropriately managed. Sports tourism and activities can be combined in Central Java. Conclusions: Combining sporting activities like river tubing, paragliding, tea gardens, and jeep communities with Kemuning Village in Ngargoyoso District, Karanganyar, Central Java, Indonesia, can help the village grow its tourism industry due to the fact that it influences the social, cultural , and economic growth of the area, promoting local advancement.